Drugs Act 1978 of Nepal: A Critical Analysis - Pathak, Nabin; Basyal, Bijaya; Jha, Prabhat Kumar; Yadav, Ujjwal; Karki, Badri; Jha, Supriya; Chalise, Mamata; Kunwar, Nisha; Adhikari, Samikshya; Ojha, Sabita; Giri, Anil (Journal of Karnali Academy of Health Sciences, 2022)
Background: With the enactment of the Drug Act in 1978, through the establishment of different bodies under the act, drug-related activities have been regulated and controlled in Nepal so as to provide safe and efficacious drugs of standard quality to the general public. However, with the overgrowing use of drugs, cosmetics, biotechnological products, nutraceuticals, and veterinary products in the present market and the present act failing to include these aspects, this paper tries to critically analyze the Drug Act 1978 of Nepal which will comprise strengths, weaknesses, opportunities, and threats faced in current scenario regarding the act. The regulation of drugs in Nepal was started with the enactment of the Drugs Act in 1978 AD, which is being carried out by the Department of Drug Administration as provisioned in the section 5 of the act. To facilitate the proper implementation of the act, various rules, regulations and guidelines are framed. The objective of this study was to explore the areas to improve in the Drugs Act and help foster the use of safe, efficacious and quality drugs. Method: The Drugs Act 1978 was critically analyzed focusing on the strengths, weaknesses, opportunities, and threats of the act as of current scenario. Result: After critically analyzing the drugs act 1978 we found out that there is lack in regulations of use of cosmetics, newer biotechnology products, nutraceuticals, veterinary product, innovative pharmaceutical products as well as the online pharmacy services. Conclusion: A major amendment and periodic revision is required with the consequence of meeting timely needs and promoting the idea of safety and efficacy in drug related activities.